Praktische Umsetzung des Gendiagnostikgesetzes (GenDG) in der Laboratoriumsmedizin, dem humangenetischen Laboratorium und der humangenetischen Beratung - Orth, Matthias; Rost, Imma; Hoffmann, Georg F.; Klein, Hanns-Georg (Laboratoriumsmedizin, 2011)
The German Genetic Diagnostics Act (GenDG) in its current version, effective since Feburary 2010, has far-reaching consequences for all physicians and also for many patients. After more than one year of experience working with the GenDG, much of the previously criticized wording has proved to be inadequate. From the beginning, experts critisised that besides the direct analysis of germline DNA, gene products should not be included in the scope of the act - potentially having a very broad impact on the entire in vitro diagnostics field. Problems with applying the act range from the impossibility to distinguish between genetic and non-genetic examinations to enormous bureaucratic hurdles which in some areas interfere with an efficient, state-of-the-art patient care (i.e., newborn screening, treatment with blood products). The rapid progress in technology, which is currently revolutionizing genetic diagnostics worldwide, has been set narrow boundaries by the German GenDG, while at the same time “personalized medicine” applying exactly the same technologies is being funded by government research grants. From the viewpoint of the concerned physicians and patients, there is an urgent need to amend the act itself and efficient action to take by the committee on genetic diagnostics (GEKO) which was appointed to define guidelines for the practical use of the GenDG.
Gesehen am 13.10.2022